Survey item nonresponse and its treatment - Rässler, Susanne; Riphahn, Regina Therese (Allgemeines Statistisches Archiv, 2006)
One of the most salient data problems empirical researchers face is the lack of informative responses in survey data. This contribution brie y surveys the literature on item nonresponse behavior and its determinants before it describes four approaches to address item nonresponse problems: Casewise deletion of observations, weighting, imputation, and model-based procedures. We describe the basic approaches, their strengths and weaknesses and illustrate their eects using a simulation study. The paper concludes with recommendations for the applied researche
WiSo-Import:2015-03-26:2655
Keywords: Item nonresponse; imputation; weighting; survey data